Defining breast cancer awareness and identifying barriers to breast cancer awareness for women with an intellectual disability: A review of the literature. (June 2022) - Walsh, Susan; O'Mahony, Mairin; Hegarty, Josephine; Farrell, Dawn; Taggart, Laurence; Kelly, Louise; Sahm, Laura; Corrigan, Maria; Caples, Maria; Martin, Anne-Marie; Tabirca, Sabin; Corrigan, Mark A.; et al.
Introduction: Incidence rates for developing breast cancer are similar for women regardless of intellectual ability. However, women with an intellectual disability present with advanced breast cancers, which often have a poor prognosis. Method: A structured narrative review of the literature was performed to explore the concepts of breast awareness and breast cancer awareness and subsequently, identify barriers to breast cancer awareness encountered by women with an intellectual disability. Results: A total of 22 studies involving people with varying levels of intellectual disability informed this review. The barriers to breast cancer awareness encountered by women with an intellectual disability include: lack of their understanding, the role of the carer and literacy issues. Conclusion: Identifying the barriers to breast cancer awareness for women with an intellectual disability will help to facilitate breast cancer awareness which has the potential to result in better long-term outcomes through an early diagnosis of breast cancer.